COMPARISON OF PROBLEMS RELATED TO THE MULTIPLICATION OF FRACTIONS IN MATHEMATICS TEXTBOOKS: THE CASE OF SINGAPORE AND TURKEY - Mersin, Nazan; Akkaş, Elif Nur (International Online Journal of Education and Teaching, 2022)
In this study, it is aimed to comparatively examine practice questions and sample solved questions about the multiplication of fractions in mathematics textbooks in Turkey and Singapore. In this direction, document analysis was used as a research method. Descriptive analysis was used in the analysis and the questions in the books were examined in seven categories: the number of steps, contextual properties, representation type, model type, meaning of multiplication, fraction type, and cognitive expectation. From the results of the analysis, it was seen that there were more questions with pure mathematical context that were solved in one step in the books in both countries. However, all kinds of fraction models are used in the questions in the Singapore textbook, whereas the length model is not used in Turkey. In addition, in fraction multiplication, the repeated addition meaning of multiplication is used only in Turkey, whereas in Singapore the operator meaning is mostly used. When examined in terms of fraction types, it was concluded that there are no examples in the form of natural numbers × fractions in the Singapore books, but that there are more problems about fraction × fraction in Singapore. When the results are evaluated in general, it is observed that the books in both countries have advantages and disadvantages compared to each other, but in terms of the categories studied the distribution in the Singapore textbook is more balanced than it is in Turkey.